Addressing the Glycine‐Rich Loop of Protein Kinases by a Multi‐Facetted Interaction Network: Inhibition of PKA and a PKB Mimic. Issue 1 (18th November 2015) - Lauber, Birgit S.; Hardegger, Leo A.; Asraful, Alam K.; Lund, Bjarte A.; Dumele, Oliver; Harder, Michael; Kuhn, Bernd; Engh, Richard A.; Diederich, François
Abstract: Protein kinases continue to be hot targets in drug discovery research, as they are involved in many essential cellular processes and their deregulation can lead to a variety of diseases. A series of 32 enantiomerically pure inhibitors was synthesized and tested towards protein kinase A (PKA) and protein kinase B mimic PKAB3 (PKA triple mutant). The ligands bind to the hinge region, ribose pocket, and glycine‐rich loop at the ATP site. Biological assays showed high potency against PKA, with K i values in the low nanomolar range. The investigation demonstrates the significance of targeting the often neglected glycine‐rich loop for gaining high binding potency. X‐ray co‐crystal structures revealed a multi‐facetted network of ligand–loop interactions for the tightest binders, involving orthogonal dipolar contacts, sulfur and other dispersive contacts, amide–π stacking, and H‐bonding to organofluorine, besides efficient water replacement. The network was analyzed in a computational approach. Abstract : The forgotten pocket : A new family of enantiopure inhibitors for protein kinase A (PKA) is reported. They complex to the ATP site, with inhibitory activities ( K i ) down to the low single‐digit nanomolar range. Besides binding to the hinge and the ribose pocket, the ligands also interact in a multi‐facetted interaction network with the glycine‐rich loop, which has been neglected in kinase inhibitor design. This network of orthogonal dipolar interactions, dispersive contacts, amide–π stacking, together with water replacement makes an important contribution to the overall ligand binding affinity.